Biventricular Unloading with Impella and Venoarterial Extracorporeal Membrane Oxygenation in Severe Refractory Cardiogenic Shock: Implications from the Combined Use of the Devices and Prognostic Risk Factors of Survival - Georgios Chatzis (Journal of Clinical Medicine, 2021)
Since mechanical circulatory support (MCS) devices have become integral component in the therapy of refractory cardiogenic shock (RCS), we identified 67 patients in biventricular support with Impella and venoarterial Extracorporeal Membrane Oxygenation (VA-ECMO) for RCS between February 2013 and December 2019 and evaluated the risk factors of mortality in this setting. Mean age was 61.07 ± 10.7 and 54 (80.6%) patients were male. Main cause of RCS was acute myocardial infarction (AMI) (74.6%), while 44 (65.7%) were resuscitated prior to admission. The mean Simplified Acute Physiology Score II (SAPS II) and Sequential Organ Failure Assessment Score (SOFA) score on admission was 73.54 ± 16.03 and 12.25 ± 2.71, respectively, corresponding to an expected mortality of higher than 80%. Vasopressor doses and lactate levels were significantly decreased within 72 h on biventricular support (p < 0.05 for both). Overall, 17 (25.4%) patients were discharged to cardiac rehabilitation and 5 patients (7.5%) were bridged successfully to ventricular assist device implantation, leading to a total of 32.8% survival on hospital discharge. The 6-month survival was 31.3%. Lactate > 6 mmol/L, vasoactive score > 100 and pH < 7.26 on initiation of biventricular support, as well as Charlson comorbity index > 3 and prior resuscitation were independent predictors of survival. In conclusion, biventricular support with Impella and VA-ECMO in patients with RCS is feasible and efficient leading to a better survival than predicted through traditional risk scores, mainly via significant hemodynamic improvement and reduction in lactate levels.